2011
DOI: 10.1186/1471-2334-11-337
|View full text |Cite
|
Sign up to set email alerts
|

Age- and region-specific hepatitis B prevalence in Turkey estimated using generalized linear mixed models: a systematic review

Abstract: BackgroundTo provide a clear picture of the current hepatitis B situation, the authors performed a systematic review to estimate the age- and region-specific prevalence of chronic hepatitis B (CHB) in Turkey.MethodsA total of 339 studies with original data on the prevalence of hepatitis B surface antigen (HBsAg) in Turkey and published between 1999 and 2009 were identified through a search of electronic databases, by reviewing citations, and by writing to authors. After a critical assessment, the authors inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
81
2
19

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 24 publications
10
81
2
19
Order By: Relevance
“…Türkiye'de HBV aşısı 1980'den beri bulunması-na rağmen, 1998'den bu yana ulusal aşılama programına dâhil edilmiş, 1999'dan bu yana da sağlık çalışanlarına uygulanmaya başlanmıştır. Sağlık çalışanlarında 1999 sonrası HBV prevalansı incelendiğinde aşılama öncesine göre düşüş görülmüştür (7,8) .…”
Section: Discussionunclassified
“…Türkiye'de HBV aşısı 1980'den beri bulunması-na rağmen, 1998'den bu yana ulusal aşılama programına dâhil edilmiş, 1999'dan bu yana da sağlık çalışanlarına uygulanmaya başlanmıştır. Sağlık çalışanlarında 1999 sonrası HBV prevalansı incelendiğinde aşılama öncesine göre düşüş görülmüştür (7,8) .…”
Section: Discussionunclassified
“…The prevalence of HBsAg positivity among patients who apply to hospitals ranges from 1.30 to 10.88%, depending on region. 15 The setting in which we conducted the study is a tertiary referral center and accepts patients from all over the country. A total of 11 patients (6.8%) had a history of known HBsAg positivity in our study.…”
Section: Discussionmentioning
confidence: 99%
“…18 Most of the adult population in many countries is not safeguarded against HBV. A recent study by Toy et al 15 has revealed that HBsAg seroprevelance in hospital setting varies between 1.30 and 10.88%, depending on the region in Turkey. The establishment of screening and vaccination protocols in high risk adult patients who are not included in vaccination programmes may prevent the spread of hepatitis B, health-care and financial losses.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of the Hepatitis B in Turkey was estimated to be 4.57%; the same value is 6.72% in our region (Eastern Anatolia) (8). On the other hand, the prevalence of Hepatitis C is relatively low in the region, and it is estimated to be around 1% (ranging between 0.6-2.2%) (9).…”
Section: Koz S Et Al : Features Of Hemodialysis In Cirrhotic Patientsmentioning
confidence: 93%